ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI IMPOR KEDELAI DI INDONESIA - Naufal Nur Mahdi; Suharno Suharno (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2019)
Domestic soybean production that has not been able to meet national soybean needs is an implication of the decline in soybean harvested area in Indonesia. The opposite condition occurs at the level of demand for soybeans which increases every year. The soybean import policy is an alternative step for the government to overcome the gap between soybean production and consumption in Indonesia. Soybeans in this study are not separated from the type, namely with HS code 1201 (Soya beans, whether or not broken). This study aims to analyze the factors that influence soybean imports in Indonesia by using secondary data from 2002 to 2017 in the form of panel data with gravity models. The data used in this study came from UN Comtrade, World Bank, CEPII, FAOSTAT, Ministry of Trade and Ministry of Finance. The estimation results show that the variables that significantly influence the volume of imports of Indonesian soybeans are the variable GDP per capita Indonesia, GDP per capita of the country of origin of imports, domestic soybean prices, domestic soybean production and soybean import tariffs.